2011
DOI: 10.1590/s0100-06832011000200026
|View full text |Cite
|
Sign up to set email alerts
|

Atributos físicos, químicos e biológicos do solo em ambientes de voçorocas no município de Lavras - MG

Abstract: RESUMO A região Sul de Minas Gerais apresenta grandes áreas comprometidas por erosões do tipo voçoroca, e a avaliação dos atributos do solo nesses ambientes é de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 13 publications
4
15
0
15
Order By: Relevance
“…Metabolic quotient values of the forests evaluated in this study are within the range found for other forest ecosystems (Behera & Sahani, 2003) and can be classified as "low" compared to environments under stress (Gomide et al, 2011). These findings indicate that the forests in this study are at a more advanced succession stage, in which the energy accumulated in the system is greater (Odum, 1983;Insam & Haselwandter, 1989;Anderson & Domsch, 1990;Kieft et al, 1998).…”
Section: Discussionsupporting
confidence: 77%
“…Metabolic quotient values of the forests evaluated in this study are within the range found for other forest ecosystems (Behera & Sahani, 2003) and can be classified as "low" compared to environments under stress (Gomide et al, 2011). These findings indicate that the forests in this study are at a more advanced succession stage, in which the energy accumulated in the system is greater (Odum, 1983;Insam & Haselwandter, 1989;Anderson & Domsch, 1990;Kieft et al, 1998).…”
Section: Discussionsupporting
confidence: 77%
“…Santo Antônio do Jardim, SP, 2015 Para a variável quociente metabólico (qCO 2 ) não houve diferença significativa entre os sistemas avaliados (Quadro 4). Porém, elevados valores de qCO 2 , como os observados neste estudo, indicam que pode estar ocorrendo maior gasto de energia para a manutenção da comunidade microbiana, ou seja, devido a uma situação de estresse ou distúrbio, possivelmente determinada pelo manejo intensivo do solo e pelo frequente uso de agrotóxi-cos, os microrganismos poderão ter que consumir mais substrato para sua sobrevivência (Carneiro et al, 2008;Silva et al, 2010;Gomide et al, 2011). Outra explicação para este resultado pode estar associada ao fato de que quocientes metabólicos elevados são um indicativo de comunidades microbianas em estágios iniciais de desenvolvimento e com maior proporção de microrganismos ativos em relação aos inativos (Roscoe et al, 2006).…”
Section: Biomassa Microbiana Do Solounclassified
“…This area (~150.18 ha) does not have either a detailed soil map or a detailed geologic map and is located between latitudes 7,651,207 and 7,653,478 m and longitudes 501,962 and 503,957 m, Zone 23 K. The climate of the region is Cwa (C: subtropical climate; w: rainy summers; a: warm summers), characterized by rainy and warm summers and cold and dry winters, according to the Köppen classification system, with mean annual temperature and rainfall of 19 °C and 1530 mm, respectively [40]. The area encompasses a great geologic variety, with the dominance of leucocratic and mesocratic gneisses, the latter containing greater contents of Fe and darker minerals than the former, as well as a gabbro intrusion and sediments of varying nature.…”
Section: Study Area and Laboratory Analysesmentioning
confidence: 99%